1998
DOI: 10.1007/s002210050476
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Müller cells after increased intraocular pressure in the rat retina

Abstract: Using light microscopy and immunocytochemistry, we investigated the morphological changes of retinal tissues and the reaction of Müller cells in the ischemic rat retina induced by increasing intraocular pressure. At early stages (from 1 h to 24 h after reperfusion), cells in the ganglion cell layer and in the inner nuclear layer showed some degenerative changes, but at later stages (from 72 h to 4 weeks) marked degenerative changes occurred in the outer nuclear layer (ONL). At 4 weeks after reperfusion, the ON… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(33 citation statements)
references
References 16 publications
2
31
0
Order By: Relevance
“…Up to 3 days, strong immunoreactivity is appeared in some Mü ller cells, and then appeared in photoreceptor cells. Previous studies have shown that transient retinal ischemia results in progressive degeneration of retinal neurons over a period of several weeks which is more pronounced in the inner retina at earlier stages, while a marked loss of photoreceptors occurs at later stages (Bü chi et al, 1991;Kim et al, 1998;Ju et al, 2000). Thus, upregulation of clusterin expression follows the time course of retinal cell damage in the ischemic retina.…”
Section: Discussionmentioning
confidence: 86%
“…Up to 3 days, strong immunoreactivity is appeared in some Mü ller cells, and then appeared in photoreceptor cells. Previous studies have shown that transient retinal ischemia results in progressive degeneration of retinal neurons over a period of several weeks which is more pronounced in the inner retina at earlier stages, while a marked loss of photoreceptors occurs at later stages (Bü chi et al, 1991;Kim et al, 1998;Ju et al, 2000). Thus, upregulation of clusterin expression follows the time course of retinal cell damage in the ischemic retina.…”
Section: Discussionmentioning
confidence: 86%
“…Neuronal cell death in the retinal ganglion cell layer (GCL) is observed as pyknotic nuclei in the GCL [25]. Glial activation is evident by up-regulation of glial fibrillary acidic protein (GFAP) in response to deleterious release of glutamate from over excited neurons after ischemia [6,7]. Retinal edema also occurs, because of the increased water transportation and accumulation as a result of increased extracellular fluid volume, increased aquaporin 4 (AQP4) immunoreactivity and swelling of retinal glial cells [8,9].…”
mentioning
confidence: 99%
“…5), and this effect was blocked by glibenclamide. Müller glial cell activation and increased GFAP expression are general phenomenon observed in ischemic-damaged neuronal tissues (28). Diazoxide, a K ATP -channel opener, reduced the activation of glial cells in brain ischemia.…”
Section: Discussionmentioning
confidence: 97%